Health Monitoring Application for Covid-19 Self-Isolation Patients - Setiawan (Scopus ID: 56829262300), Eko Budi (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The self-isolation procedure must be carried out under the supervision of a local health facility which is part of the Covid-19 handling post so that the health condition of the patient can continue to be monitored while undergoing self-isolation. However, in practice, supervision of this self-isolation patient is often neglected, resulting in many patients experiencing deteriorating health conditions and being given treatment late which leads to death. The purpose of this research is to create an android-based application that can be used to monitor the health condition of patients who are undergoing self-isolation. This application was developed using the Java and Kotlin programming languages, the Firebase Realtime Database, and several technologies, namely Smartband, Bluetooth Low Energy, Google Maps API, Google Places API, Firebase Cloud Messaging, Covid-19 Indonesia API, RS Bed Covid-19 Indonesia API and Indonesia News API. The software development method used is the waterfall method. Based on the results of alpha testing using the black-box method, it can be concluded that the application built meets the requirements and works according to its functional requirements. Meanwhile, based on the results of beta testing using the questionnaire method given to 6 respondents with a Likert scale calculation, the percentages for each question were 100%, 93.33%, and 93.33%, so it can be concluded that the application built has achieved the desired goals.